Kritik Pemikiran Taqiyyudin Al-Nabhani tentang Zakat Uang Kertas - Ri fa'i (Rumah Jurnal Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2018)
Money is usability standard contained in the goods and labor. Money can be classified into two types, namely coins and paper money. Coin money is made ​​of minerals such as gold, silver, copper, tin and nickel. Paper money is money which is made ​​of paper, as a replacement of gold or silver or made ​​of a mixture of gold or silver or a mixture of both is secured wholly or partly by gold and silver. Paper money as a kind of currency that existed at this time has dominated the economy and replaced the gold and silver as a means of exchange. By the money, the actors of economic can conduct transactions anytime, anywhere, and with anyone easily and efficiently. This will certainly lead to the rapid development of the real sector, because it is considered an asset that can be used as a means of exchange and received by the general public, the Al-Nabhani charity requires it. In the excavation of law relating to zakat of paper money, al-Nabhani used the literal approach and used the method of qiyas. The lawyer-as the basis of qiyas are passages that describe the zakat of gold and silver as well as the Hadith that shows about currency and valuables, such as word riqqah, wariq, dinars and dirhams, hadith about diyat, and prohibition ihtikar. The essence of Allah forbade the hoarding of gold and silver, and ordered to remove the charity from both. The money is legal equated with gold and silver because there are 'illat that on the day of the gold and silver that paragraph applies as currency, in addition to his position as a mineral that has essential value. 'Illat is justifiable because history proves that gold and silver are the currency used to trade through out the life of the Prophet and the caliphs afterwards.